(untitled) (Transport systems and technologies, 2018)
Mathematical models of a bridge crane with frequency control of an electric drive of movement, based on a three-mass and four-mass design schemes are described in the article. The developed software for realization of the specified mathematical models is presented. It allows to integrate differential equations describing the motion of multi-mass dynamic crane models using the Runge-Kutta numerical method and to calculate the displacements, speeds and accelerations of all the reduced masses, the dynamic loads on the drive and the crane’s metal structures, as well as the dynamic loads on cargo at each step of the specified time interval. The maximum values of these loads at each stage of the transient process and the time of their occurrence are determining. The results of calculations are displayed on the screen in the form of a table and graphs of the transient processes of the bridge crane (including frequency controlled crane). The analysis of changes in kinematic and dynamic parameters during braking of a bridge crane of the carrying capacity of 20/5 tons with frequency control of the drive of movement is performed using the developed computer program and theory of experiment planning. Polynomial dependencies of dynamic loads on the crane’s metal structure and the dynamic loads on cargo, as well as the crane braking time from the frequency control parameters, are constructed. The graphs of equal response of the dynamic loads acting on the crane metal structure and the dynamic loads acting on the cargo when braking the frequency-controlled overhead crane are given for practical applications.